2004
DOI: 10.1016/j.ssc.2004.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carrier density gradients on magnetotransport data measured in Hall bar geometry

Abstract: We have measured magnetotransport of the two-dimensional electron gas in a Hall bar geometry in the presence of small carrier density gradients. We find that the longitudinal resistances measured at both sides of the Hall bar interchange by reversing the polarity of the magnetic field. We offer a simple explanation for this effect and discuss implications for extracting conductivity flow diagrams of the integer quantum Hall effect.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…2 has been observed before in large, macroscopic, Hall-bar shaped samples, and has been attributed to the existence of a longitudinal densitygradient in the samples [12]. Recently, Ponomarenko et al and Karmakar et al [13] reported on the observation of this symmetry and suggested a model that details how the symmetry originates from a density gradient. Due to a longitudinal density-gradient in their samples the 'left' and 'right' Hall resistances of the samples are not equal, R l H = R r H , and are instead found to be B-shifted with respect to each other.…”
mentioning
confidence: 64%
“…2 has been observed before in large, macroscopic, Hall-bar shaped samples, and has been attributed to the existence of a longitudinal densitygradient in the samples [12]. Recently, Ponomarenko et al and Karmakar et al [13] reported on the observation of this symmetry and suggested a model that details how the symmetry originates from a density gradient. Due to a longitudinal density-gradient in their samples the 'left' and 'right' Hall resistances of the samples are not equal, R l H = R r H , and are instead found to be B-shifted with respect to each other.…”
mentioning
confidence: 64%
“…Most of the studies on these aspects are on 2D semiconductor devices (see for instance Ref. 30 and reference therein), while little discussion is dedicated to graphene. In graphene, it is common practice 20,22 to perform a symmetrization of the data with respect to magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…This variation leads to a charge density gradient in the graphene layer, which is known to affect the experimental data curves. 30 For linear density variations in the longitudinal direction, the best resistance estimate is obtained by averaging the values measured at opposite sides of the device. 31 The residual small tilt in the data of Fig.…”
mentioning
confidence: 99%
“…18 When such a gradient exists, it induces a directional change in the HE and thus it contributes to a change in the voltage drop measured between two points on the same side of the current path. Therefore, the antisymmetric contribution behaves as the difference between the HE signals with different carrier densities.…”
mentioning
confidence: 99%